A prospective observational cohort study of HIV infection in Indonesia: baseline characteristics and one-year mortality - Tuti P. Merati; Evy Yunihastuti; Rudi Wisaksana; Nia Kurniati; Dona Arlinda; Muhammad Karyana; Nugroho H. Susanto; Dewi Lokida; Herman Kosasih; Aly Diana; Lois E. Bang; Melinda Setiyaningrum; et al. (BMC Infectious Diseases)
Abstract Introduction The incidence rate of newly diagnosed HIV infection in Indonesia decreased from 21 per 100,000 in 2011 to 10 per 100,000 in 2021. Despite this progress, AIDS-related deaths among people living with HIV (PLWH) increased from 3.4% in 2010 to 4.8% in 2020. Determining risk factors for mortality may identify areas to intervene and reduce mortality. Methods A multicenter, prospective, observational cohort study of HIV infection, coinfections, and comorbidities (INA-PROACTIVE) was carried out at 19 hospitals across major islands in Indonesia. The study enrolled PLWH from 2018–2020 and followed them for 3 years. For this analysis, PLWH ≥ 18 years old with one year of follow-up data were included. Cox regression was used to identify variables at enrollment that correlated with one-year mortality. Results Among the 4,050 PLWH analysed in the study, 68.8% were male, 53.5% acquired HIV through heterosexual transmission, 92.4% were on antiretroviral treatment (ART) at enrollment, and 72.4% had an undetectable viral load. At one year, 115 (2.8%) had died. Detectable viremia at enrollment was significantly associated with mortality, with the risk increasing as the viral load (VL) category increased (adjusted hazard ratio [aHR] 4.47, 95% CI: 1.47–13.56 for VL 50 to < 1,000 copies/mL; aHR 7.88, 95% CI: 2.80–22.20 for VL 1,000 to 10,000 copies/mL; and aHR 18.33, 95% CI: 7.94–42.34 for VL > 10,000 copies/mL; compared to VL < 50 copies/mL). Other factors at enrollment significantly associated with mortality were a CD4 + count < 200 (aHR 8.02, 95% CI: 2.69–23.86; compared to ≥ 350), age 40–49 years (aHR 2.19, 95% CI 1.23–3.87; compared to 18–29 years) and being underweight (aHR 1.84, 95% CI: 1.18–2.85; compared to normal weight). Conclusions Among predominantly treatment-experienced PLWH, detectable viremia and continued immunosuppression were significantly associated with one-year mortality. This study highlights the importance of ART with complete viral suppression as well as immune recovery to prevent mortality. Trial registration Clinical Trial Number: NCT03663920, registration date: 4 January 2018.